Factors associated with relapse amongst substance abusers - Shah Mohammad Ashek Uddin Bhuiyan,; M. Azizul Islam,; A. H. M. Kazi Mostofa Kamal,; Mahbuba Akhter Jahan, (International Journal of Research in Medical Sciences, 2023)
Background: Relapse amongst substance abusers is common throughout the world, and Bangladesh is no exception to this. In Bangladesh, drug related problems are gradually becoming a burning issue in context of social, economical and medical perspective. The present study aimed to find out factors indicating relapse amongst substance abuser. Methods: This descriptive type of observational study was conducted in the combined military hospital and other government/private hospital/institute, especially the central drug addict treatment center, Dhaka. Informed consent was obtained prior to data collection. Collected data was classified, edited, coded, and entered into the computer for statistical analysis by using SPSS-23. The chi-Square test was used to analyze the categorical variables, and a p<0.05 was considered as statistically significant. Results: The study involved 100 patients who had a history of substance abuse. The most common substance abused was Yaba (27%), followed by cannabis (21%). The average duration of abuse for Yaba was 5.8 years, while the longest mean duration was for Alcohol (14.2 years). In the 2nd admission, the largest percentage of patients was aged 21-30 years and were male. The majority of patients were Muslim and were either unemployed or had a lower socioeconomic status. Patients age, occupation, socioeconomic status, peer pressure, and family problems all had a significant association (p<0.05) with relapse at different admissions. Peer pressure and family problems were also identified as factors affecting relapse, with 67.57% and 56.76% of patients experiencing them during their 2nd admission, respectively. Conclusions: The study found Yaba to be the most commonly used drug, followed by cannabis, phensedyl, heroin, etc. Alcohol was found to have the longest duration of abuse. Most patients were aged 21-30 and unemployed in multiple admissions. Peer pressure and unemployment were major factors in substance abuse, and psychiatric illness was a common factor in relapse. The results align with global findings and highlight the need for a comprehensive approach to addressing substance abuse, considering all relevant factors.